FORMULASI DAN UJI SIFAT FISIKOKIMIA SEDIAAN LOSIO DENGAN BERBAGAI VARIASI KONSENTRASI VITAMIN E - ., Ririn Karina H (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Vitamin E is an antioxidant that can bind with oxygen to destroys free radicals. Vitamin Ein tissues suppress oxidation of unsaturated fatty acids, which helps and maintain cell membranefunction. This research was aimed to find out the optimum formulation of lotion vitamin E andalso to determine the levels of vitamin E in lotion once it was made. The formula of lotion wasmade with series of five concentrations of vitamin E those are 1%, 2%, 3%, 4%, and 5%. Theoptimum formula is chosen based on two physicochemical properties parameters, pH andviscosity. Analysis of data was performed using program R i386 3.1.1 package R-commander. Theresults showed that formula E (contained concentration 5%) was selected as the optimum formulawith spreading capacity of 6,97 cm; adhesive force 38,33 s; pH 7,38; and the viscosity 38,67 P. Ccolumn was used in this research for HPLC condition. Validation result from the analysis methodused standard levels series displaying correlation coefficient (r) of 0,9973; relative standarddeviation (RSD) ≤ 16 %; percentage of recovery 92,16 %; limit of detection (LOD) 1,725 µg/mL;and limit of quantitation (LOQ) 5,752 μg/mL. The result of vitamin E levels obtained by HPLCare 3,956 %. Keywords: Vitamin E, alpha tocopherol, Losio, Lotion, High Performance LiquidChromatography, HPLC